The Fabrication of Lithium Niobate Nanostructures by Solvothermal Method for Photocatalysis Applications: A Comparative Study of the Effects of Solvents on Nanoparticle Properties - Mohd Al Saleh Alothoum; Chawki Awada (Ceramics)
In this work, we report, for the first time, a comparative study on the effects of different solvents on the properties of LiNbO3 (LN) nanostructures. The solvothermal synthesis method was successfully used with three different solvents: 1—water, 2—methanol, and 3—benzyl. The structural and optical properties of the as-prepared nanoparticles were studied using transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-Vis absorbance, Raman spectroscopy, and photoluminescence (PL). Nanoparticles of a very small size, with an average size between 3 and 10 nm, were obtained for the first time. The photocatalytic activities of the three synthesized LiNbO3 nanoparticles were studied in relation to the photodegradation of a complex and heavy reactive black 5 dye for a wastewater treatment application. The LiNbO3 synthesized with deionized water showed a higher photocatalytic activity than those synthesized using other solvents, such as methanol or benzyl.